2016
DOI: 10.1051/bioconf/20160702017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pre-fermentative treatments on the volatile, chromatic features, organic acids and phenolic content of Fetească albă Romanian wine

Abstract: Abstract. The present study evaluates the influence of some pre-fermentative treatments on the volatile content, the chromatic parameters, the total polyphenol index and Folin-Ciocâlteu index of experimental wines obtained from Feteascȃ albȃ grape variety. Five experimental samples were produced: FA V0 (control sample), FA V1 (sodium bentonite treatment), FA V2 (glutathione treatment), FA V3 (tannin treatment), FA V4 (oenological coal treatment). The use of pre-fermentative treatments show lower values of Foli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Previous studies [26][27][28] showed similar results on sparkling wines and are in accordance with other literature data [29].…”
Section: Physicochemical Characteristics Of Winessupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies [26][27][28] showed similar results on sparkling wines and are in accordance with other literature data [29].…”
Section: Physicochemical Characteristics Of Winessupporting
confidence: 92%
“…The lowest values of tartaric acid were identified in V4 and V5, in which the fermentation took place in tanks, which may be due to a considerable increase in ethanol during the fermentation stage, combined with low fermentation temperature. Comparable values of tartaric acid were obtained by Moros , anu et al [27]. Bayraktar [10] reported a positive correlation between tartaric acid concentration and citric acid in wine.…”
Section: Organic Acid Concentrationsmentioning
confidence: 62%
“…Also, Merlot wines from the south-east region aged for 12 months (Table 3) contained a higher quantity of ethyl decanoate compared with the samples aged for 6 months ( Table 2). The presence of esters in higher concentrations in wines from the south-east region compared to those from the north-west region might be explained by the different environmental conditions [38].…”
Section: Estersmentioning
confidence: 99%
“…The volatile compounds are usually extracted by different methods, such as solid-phase extraction [32], solid-phase micro-extraction [33], stir bar sorptive extraction [34], or liquid-liquid extraction methods using organic solvents [35] before the gas chromatographic analysis. There are few data available for the volatile compounds of the international grape varieties grown in Romania and wines, but also for Romanian grape varieties and wines [36][37][38]. Fetească Neagră is one of the most widespread and economically important cultivars grown in Romania [39].…”
Section: Introductionmentioning
confidence: 99%